Corruption and economic growth: New empirical evidence - Klaus Gründler; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The nexus between corruption and economic growth has been examined for a long time. Many empirical studies measured corruption by the reversed Transparency International's Perception of Corruption Index (CPI) and ignored that the CPI was not comparable over time. The CPI is comparable over time since the year 2012. We employ new data for 175 countries over the period 2012-2018 and re-examine the nexus between corruption and economic growth. The cumulative long-run effect of corruption on growth is that real per capita GDP decreased by around 17% when the reversed CPI increased by one standard deviation. The effect of corruption on economic growth is especially pronounced in autocracies and transmits to growth by decreasing FDI and increasing inflation.
Keywords: C23; H11; K40; O11; 330; Perceived corruption; economic growth; panel data